2006
DOI: 10.1021/jf053001p
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Odor-Active Volatile Compounds of Fresh and Smoked Salmon

Abstract: The odorant volatile compounds of raw salmon and smoked salmon have been investigated by two gas chromatography-olfactometry methods (frequency detection and odorant intensity) and gas chromatography-mass spectrometry. After simultaneous steam distillation-solvent extraction with diethyl ether and the recovery of the aromatic extract in ethanol, qualitative olfactometric characterization and identification followed by a quantitative assessment of the odorant volatile compounds were carried out. The origin of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(154 citation statements)
references
References 43 publications
4
147
0
3
Order By: Relevance
“…Very recently, we tried to identify functional groups serving as structural elements for recognition by CD36 using (Z)-9-octadecenoic acid as a reference standard (27). We thus found that the aldehyde counterpart (Z)-9-octadecenal (or oleic aldehyde, an odor-active volatile compound found in foods such as smoked salmon) (29) and another species of fatty aldehydes, (Z)-11-hexadecenal (a volatile pheromone used in distinct species of insects) (8), could serve as ligands for the receptor. However, there are still the two examples of odor-active volatiles recognizable by CD36.…”
Section: Preparation Of Test Compoundsmentioning
confidence: 99%
“…Very recently, we tried to identify functional groups serving as structural elements for recognition by CD36 using (Z)-9-octadecenoic acid as a reference standard (27). We thus found that the aldehyde counterpart (Z)-9-octadecenal (or oleic aldehyde, an odor-active volatile compound found in foods such as smoked salmon) (29) and another species of fatty aldehydes, (Z)-11-hexadecenal (a volatile pheromone used in distinct species of insects) (8), could serve as ligands for the receptor. However, there are still the two examples of odor-active volatiles recognizable by CD36.…”
Section: Preparation Of Test Compoundsmentioning
confidence: 99%
“…Iglesias and Medina (2008) reported that propanal, 1-penten-3-ol, 2,3-pentanedione, hexanal and 1-octen-3-ol were the main volatile compounds formed during the storage of Atlantic horse mackerel muscle at 4°C. Varlet et al (2006) reported that carbonyl compounds including 4-heptenal, octanal, decanal, and 2,4-decadienal were responsible for the fishy odour of salmon flesh. Alcohols including 1-penten-3-ol, 1-octen-3-ol, 2-ethylhexanol and 1-hexadecanol were lower in P1-1U than the remaining samples (Table 2).…”
Section: Volatile Compounds Of Gelatin Hydrolysatementioning
confidence: 99%
“…1-Octen-3-ol is considered as a degradation product of linoleic acid hydroperoxides [20]. These compounds have been previously reported as odor-active compounds in crabs species [12] and other aquatic foods, such as smoked salmon [30], and scallops [31]. 2-Ethylpyridine was found to be closely associated with claw meat, which might be affected by its relatively higher intensity score in the GC-O study.…”
Section: −1mentioning
confidence: 81%